(untitled) (Comparative & International Education Series, 2021)
“A must-read for all interested in the quality of higher education at an HBCU. Internationalization has long been an integral part of the HBCU history at institutions like Hampton University. This is a timely platform to share the unique ways that the HBCUs have built their institutions on the value of the inclusion of a global population. JoAnn W. Haysbert, Chancellor and Provost, Hampton University, Virginia (USA) "This timely book explores the outstanding legacy of global engagement to be found at the nation’s historically Black colleges and universities. Higher education leaders at all types of institutions will find the discussion of best practices for internationalization and international initiatives at HBCUs to be both useful and inspiring.” Freeman A. Hrabowski, President, University of Maryland, Baltimore County (USA) This book brings out a unique advantage of HBCUs for engaging internationally in an interdependent world undergoing transformative globalization and structural realignment. It contains scholarship showing that HBCUs are indispensable for providing the world with a much fuller education/understanding of the United States, with its complex history, its current issues, and its future possibilities for unity and international engagement. Gerard A. Postiglione, Emeritus Professor of Higher Education, The University of Hong Kong (HK) Examining within HBCU’s the three critical tools of internationalization -study abroad, international student enrollment, and integration of the global throughout an institution-, this book offers invaluable theoretical and practical insights to those of us aspiring to institutionalize our HBCUs. Roger Anderson , Assistant Professor of International Languages & Cultures, Central State University- Wilberforce, Ohio (USA) "Historically Black Colleges and Universities are uniquely positioned to teach students from historically marginalized communities about the importance of global citizenship. This book provides a clear pathway for establishing robust internationalization initiatives and international education programming at HBCUs." Mary McConner, American Council on Education Fellow, Grand Valley State University, Michigan (USA) HBCU students deserve the best opportunities and internationalization of the curriculum and campus is essential to their growth and future opportunities. In Reimagining Internationalization and International Initiatives at Historically Black College and Universities, Bista and Pinder provide a road map for rethinking internationalization at HBCUs and doing it with purpose, a nod to culture, and an innovative spirit. Marybeth Gasman, Samuel DeWitt Proctor Endowed Chair in Education & Distinguished Professor, Rutgers University, New Jersey (USA) With much excitement, I endorse this book, which fills an existing literature gap in the field of Curriculum Internationalization and International initiatives at Historical Black Colleges and Universities(HBCUs). It draws a wealth of knowledge from highly experienced and astute scholars in the field, covering cogent critical topics, including the peculiar impact of COVID-19 on HBCUs. This volume is a great resource for international education researchers and scholars. Nneka Nora Osakwe, Professor of English, former Director of International Education, Albany State University, Georgia (USA) "Through expert research and scholarship, this compilation shines a light on a vital sector of international education in the United States. This timely publication serves as a testament to the persistent efforts toward comprehensive internationalization on HBCU campuses across the country, broadening access and inclusion for African Americans, and expanding the context for global learning." Dafina Blacksher Diabate, Director, Office of International Programs Lincoln University, Pennsylvania (USA) Reckoning with the racial inequalities within International Education is long overdue, and Reimagining Internationalization and International Initiatives at Historically Black Colleges and Universities has taken an important step in that direction. This book is the first to bring together and analyze all of the data around international education among HBCUs in one place, along with offering inspiring examples and recommendations on how to increase participation among students of color. I believe this book will spur leaders and practitioners of international education across all institutions within the United States to set new goals, objectives and metrics to account for and remedy the inequities on their own campuses. Ross Lewin, Associate Vice President for International Affairs, University of Maryland, Maryland (USA)